2009
DOI: 10.1007/s11547-009-0450-2
|View full text |Cite
|
Sign up to set email alerts
|

Atypical appendicitis: diagnostic value of volume-rendered reconstructions obtained with 16-slice multidetector-row CT

Abstract: In patients with atypical appendicitis, VR and cVR reconstructions increase the accuracy of MDCT in relation to the reader's experience and reduce the number of false negative results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…When grouped by modality, there were nine articles on US, composed of six articles on 548 children (9,11,(32)(33)(34)(35) and three articles on 169 adults (36)(37)(38); 20 articles on CT, composed of nine articles on 1498 children (9,26,(39)(40)(41)(42)(43)(44)(45) and 11 articles on 1027 adults (25,37,(46)(47)(48)(49)(50)(51)(52)(53)(54); and 11 articles on MRI, composed of five articles on 287 children (39,(55)(56)(57)(58), one article on 223 adults (59), and five articles on 204 pregnant women (for a total of 427 patients) (24,(60)(61)(62)(63). Figure 1 shows the article selection process.…”
Section: Literature Search and Article Selectionmentioning
confidence: 99%
“…When grouped by modality, there were nine articles on US, composed of six articles on 548 children (9,11,(32)(33)(34)(35) and three articles on 169 adults (36)(37)(38); 20 articles on CT, composed of nine articles on 1498 children (9,26,(39)(40)(41)(42)(43)(44)(45) and 11 articles on 1027 adults (25,37,(46)(47)(48)(49)(50)(51)(52)(53)(54); and 11 articles on MRI, composed of five articles on 287 children (39,(55)(56)(57)(58), one article on 223 adults (59), and five articles on 204 pregnant women (for a total of 427 patients) (24,(60)(61)(62)(63). Figure 1 shows the article selection process.…”
Section: Literature Search and Article Selectionmentioning
confidence: 99%
“…Abdominal CT is superior at demonstrating the atypically located appendix and appendicitis mimickers, such as diverticulitis, neoplasm, epiploic apandigitis, appendiceal mucoceles, and terminal ileitis [4,10]. The previous studies have shown that CT has higher sensitivity and specificity than US (91 and 90%, 78 and 83%, respectively) [8,9,11]. …”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that using enteric contrast material is unnecessary, because it does not increase sensitivity or specifity in acute appendicitis diagnosis [9]. Recent advances in CT imaging with multidetector devices, multiplanar reconstructions and volume rendering by using isotropic voxels, have improved the image quality and eased the visualisation of the appendix and inflammation [8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients usually present with moderate abdominal pain that does not worsen or shift. Atypical clinical presentation of appendicitis is more frequent in certain patient groups (elderly, pregnant women, and particularly in patients with anatomical variations of the vermiform appendix relative to the cecum) and may result in diagnostic confusion, and risk of complication such as appendiceal perforation with abscess formation, peritonitis, and bowel obstruction [4][5][6]. A prompt diagnosis is rewarded by marked decrease in morbidity and mortality [7].…”
Section: Introductionmentioning
confidence: 99%